Transformational Leadership And Nurses’ Citizenship Behavior: The Mediating Effects of Organizational Culture and Commitment In a Public Hospital of East Kalimantan Indonesia - Saputra, Randi; Ilmi, Zainal; Gani, Irwan (Al-Makki Publisher, 2025)
High-quality healthcare depends not only on clinical competence but also on nurses’ willingness to engage in behaviors that exceed formal job expectations, known as organizational citizenship behavior (OCB). This study examines how transformational leadership influences nurses’ OCB through the mediating roles of organizational culture and organizational commitment at RSUD Inche Abdoel Moeis Samarinda, a regional public hospital in East Kalimantan, Indonesia. Using a quantitative approach with a cross-sectional survey of 155 nurses, data were analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that transformational leadership significantly strengthens organizational culture and commitment, both of which positively affect nurses’ OCB. Organizational culture enhances teamwork, trust, and initiative, while organizational commitment fosters loyalty and responsibility. Moreover, the indirect effects indicate that transformational leadership influences OCB primarily through culture and commitment, suggesting a dual mediation mechanism. These findings expand the theoretical understanding of leadership-driven behavioral outcomes and highlight the importance of cultivating supportive cultural values and emotional bonds within public healthcare institutions. Practically, hospital leaders should reinforce transformational leadership practices, participatory communication, and fair recognition systems to build stronger organizational culture and commitment, thereby promoting proactive, patient-centered behavior among nursing staff.